BAHASA ARAB BAKU DAN MODERN / AL-‘ARABIYAH AL-MU’ASHIRAH (Sebuah Alternatif ) - Raden Taufikurrahman; Raden Taufiqurrahman (IAIN MADURA, 2015)
Among as many as the problem of Arabic learning is availability of textbook to language learner itself. Not only that, more than that the textbook must answer the problem of language that is faced, and the material authenticity be the main review. The book “Bahasa Arab Baku dan Modern” by Prof. DR. Eckehard Schulz is one of Arabic textbook that is written by the author to answer the problem of language which is faced by Arabic learner that is related with four skills in language with short time, and with up dated topic and material